Occurrence of genital ulcer due to herpes simplex virus type-1 (HSV-1) in attendees of a regional centre for sexually transmitted infections, central India: how disturbing is it? - P., Thenmozhi; Mukhi, Jayesh I.; Sharma, Manisha; Deogade, Kalindi S.; Gosavi, Sonali S.; Agarwal, Vandana A. (International Journal of Research in Medical Sciences, 2023)
Background: Genital herpes is caused predominantly by Herpes simplex virus type 2 (HSV-2) and less commonly by HSV-1. Genital HSV-1 infection results from oral sex, with fewer recurrences, mild symptoms, less asymptomatic shedding and poor genital transmission. The present study was undertaken to identify frequency of occurrence of HSV-1 and HSV-2 in genital herpes by microscopy, serology and Real Time Polymerase Chain Reaction (RT-PCR). Methods: Genital ulcer swabs and serum were collected at regional STI centre, Govt Medical College and Hospital, Nagpur. A total of 53 patients of Genital Ulcer Disease from December 2020 -22 were examined for etiology by microscopy, serum IgM and IgG against HSV-1 and 2 by ELISA and HSV-1 and 2 DNA by RT- PCR. Results: Out of 53 genital swabs processed, 6 (11.3%) and 28 (52.8%) samples were positive for HSV-1 and 2 DNA respectively. Of the 6 HSV-1 DNA positive samples, seropositivity for HSV-1 IgM was in 2 (33.3%) samples and for HSV-1 IgG in 4 (66.7%) samples. Of the 28 HSV-2 DNA samples, HSV-2 IgM was positive in 4 (14.3%) samples and HSV-2 IgG was positive in 7 (25%) samples, multi nucleated giant cells were seen in 2 (7.14%) samples. The remaining 15 (53.6%) HSV-2 DNA positive samples were seronegative. Conclusions: HSV-1 was detected in 6 (11.3%) samples. Though these genital ulcers may be mild, it is important to counsel the patients for abstinence or safe sex practices to prevent their partners from acquiring painful non-genital ulcers due to HSV-1.